Microwave-assisted synthesis of carbon-based nanomaterials from biobased resources for water treatment applications: emerging trends and prospects - Adeola, Adedapo O.; Duarte, Michelle P.; Naccache, Rafik (Frontiers in Carbon, 2023)
Carbon-based nanomaterials have drawn significant interest as desirable nanomaterials and composites for the adsorptive removal of various classes of pollutants from water owing to their versatile physicochemical properties. The underlying sorption mechanisms serve as the bedrock for the development of carbonaceous adsorbents for various target pollutants. Microwave-assisted synthesis can be regarded as a recent and well-advanced technique for the development of carbon-based nanomaterials, and the use of biobased materials/wastes/residues conforms with the concept of green and sustainable chemistry. For advancements in carbon-based functional nanomaterials and their industrial/field applications, it is essential to fully comprehend the sorption performance and the selective/non-selective interaction processes between the contaminants and sorbents. In this regard, research on the development of carbon-based nanomaterials for the adsorption of chemical contaminants, both organic and inorganic, in water has made considerable strides as discussed in this review. However, there are still several fundamental hurdles associated with microwave-assisted chemical synthesis and commercial/industrial scale-up applications in nano-remediation. The challenges, benefits, and prospects for further research and development of carbon-based nanomaterials/nanocomposites for the purification of water are also discussed.